2011
DOI: 10.1130/g32237.1
|View full text |Cite
|
Sign up to set email alerts
|

Fracturing of the Panamanian Isthmus during initial collision with South America

Abstract: Tectonic collision between South America and Panama began at 23-25 Ma. The collision is signifi cant because it ultimately led to development of the Panamanian Isthmus, which in turn had wide-ranging oceanic, climatic, biologic, and tectonic implications. Within the Panama Canal Zone, volcanic activity transitioned from hydrous mantle-wedge−derived arc magmatism to localized extensional arc magmatism at 24 Ma, and overall marks a permanent change in arc evolution. We interpret the arc geochemical change to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
289
4
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(316 citation statements)
references
References 32 publications
14
289
4
9
Order By: Relevance
“…Although a Late Pliocene date for final closure is now well constrained and strongly supported by several lines of independent evidence, the form, elevation and degree of subaerial emergence of the southern tip of Central America after it collided with South America approximately 24 Ma (Farris et al, 2011) remains unresolved (Kirby and MacFadden, 2005;Retallack and Kirby, 2007;Schmidt, 2007;Molnar, 2008). Uplift rates based on paleobathymetries of marine sediments from across the Isthmus suggest that the majority of the volcanic arc was submerged up until very recently with bathyal sediments of latest Miocene age present in the Caribbean and Pacific of western Panama, the Caribbean of central Panama and eastern Panama (Coates et al, 1992;Collins, 1992Collins, , 1993Collins, , 1996Coates, 1999;Coates et al, 2000Coates et al, , 2003Coates et al, , 2004Coates et al, , 2005.…”
Section: Sequence Of Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a Late Pliocene date for final closure is now well constrained and strongly supported by several lines of independent evidence, the form, elevation and degree of subaerial emergence of the southern tip of Central America after it collided with South America approximately 24 Ma (Farris et al, 2011) remains unresolved (Kirby and MacFadden, 2005;Retallack and Kirby, 2007;Schmidt, 2007;Molnar, 2008). Uplift rates based on paleobathymetries of marine sediments from across the Isthmus suggest that the majority of the volcanic arc was submerged up until very recently with bathyal sediments of latest Miocene age present in the Caribbean and Pacific of western Panama, the Caribbean of central Panama and eastern Panama (Coates et al, 1992;Collins, 1992Collins, , 1993Collins, , 1996Coates, 1999;Coates et al, 2000Coates et al, , 2003Coates et al, , 2004Coates et al, , 2005.…”
Section: Sequence Of Eventsmentioning
confidence: 99%
“…The formation of the Isthmus of Panama stands as a model in paleooceanographic and evolutionary studies (Coates and Obando, 1996;Jackson and Budd, 1996;Haug and Tiedemann, 1998;Lessios, 2008) yet there remain many uncertainties regarding the paleoclimate, paleogeography and the timing and rates of uplift of the Isthmus during its formation (Schmidt, 2007;Farris et al, 2011;Montes et al, 2012). Today, the topography of the Central American Isthmus strongly dictates the marine oceanic environments of the Tropical Eastern Pacific (TEP).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are congruent with some findings of Bacon et al (2015), who obtained in their analyses organisms that probably passed through the Panama isthmus circa 20 Ma. Recent models suggest an early start for the isthmus formation in the Oligocene (Montes et al, 2012) or near to 25 to 23 Ma (Farris et al, 2011). Studies based on biological evidence indicate a formation between 3.5 to 3 Ma, while bathimetric evidence supports a formation approximately between 14 and 12 Ma (Duque-Caro, 1990;Coates et al, 1992Coates et al, , 2004).…”
Section: Geological Scenariomentioning
confidence: 99%
“…According to Gregory-Wodzicki (2000), the Eastern Cordillera was at no more than 40% of its modern elevation by 4 Ma and an intensified uplift (circa 4-5 to 3 Ma) has been associated with the South American-Panama collision (Farris et al, 2011). However, Podocnemis (Vargas-Ramirez et al, 2008) showed a vicariant node involving two species separated around 15 Ma and the Annonaceae family presented a Caribbean node separated from the Amazonian node between 20 to 15 Ma.…”
Section: Geological Scenariomentioning
confidence: 99%
“…A rapid increase in relative sea level could be explained by an increase in eustatic sea level and/ or an increase in America during the late Oligocene/early Miocene (Weber et al, 2010;Escalona and Mann, 2011;Farris et al, 2011) could also be responsible for this deepening. During the Oligocene-early Miocene, tectonic subsidence increases in western Venezuela (Falcón area) thus extending the Falcón Basin to the south and E-W (Escalona and Mann, 2011).…”
Section: Oligocene/miocene Transition In the Cocinetas Basinmentioning
confidence: 99%